2014
DOI: 10.5505/kjms.2014.65365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education on mothers' capability of identification of safety precautions of home accidents

Abstract: AIM:The purpose of this study was to investigate the effect of planned training, provided for mothers with 0-6 year old children, on their identifi cation of safety precautions for home accidents. METHODS:The experimental design with pretest-posttest control group was used in the study. The data of the study was collected from 160 mothers who were registered to four family health centers in the city center of Kars, between February 2013 and May 2013 GirișBir konutun içinde ya da çevresinde meydana gelen kaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
1
10
0
6
Order By: Relevance
“…The frequency of home accidents significantly increased as the education level of mothers decreased (13). Çapık and Gürol found that mothers with higher education had more knowledge and attitudes towards home accidents, and of their prevention (9). Similarly, in the present study, we found that mothers with high school education or above were more aware of home accidents, used safety precautions more frequently inside the house, and their scale score of knowledge of precautionary measures against home accidents was higher.…”
Section: Discussionsupporting
confidence: 84%
“…The frequency of home accidents significantly increased as the education level of mothers decreased (13). Çapık and Gürol found that mothers with higher education had more knowledge and attitudes towards home accidents, and of their prevention (9). Similarly, in the present study, we found that mothers with high school education or above were more aware of home accidents, used safety precautions more frequently inside the house, and their scale score of knowledge of precautionary measures against home accidents was higher.…”
Section: Discussionsupporting
confidence: 84%
“…We concluded that, not the formal education but taking a specific education about home accidents increase preventive measures against home accidents. Therefore, a structured education specifically addresses home accidents is very important to increase the quantity and quality of preventive measures against home accidents (26). This education should comprehensively cover the most common (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the sample size, the effect size of a previous study on a similar topic was used. Using the data of the study named "The effect of education on the ability of mothers to identify safety measures for home accidents" conducted by Çapık and Gürol in 2014, the alpha error level was found to be 0.05, the effect size was 0.93, and the sample size was 24 when the power was taken as 99% (18). The inclusion criteria were considered as (a) having a child with ID, (b) living with her child, (c) and the mother does not have any hearing, speaking, understanding or mental problems and (d) willingness to participate in the study.…”
Section: Setting and Sample Selectionmentioning
confidence: 99%
“…Therefore, it is the responsibility of adults to provide a safe environment for these children, to take protective measures and to control the safety of their living areas (12,13). In studies conducted in Turkey, the families have been reported to have insufficient knowledge about the prevention of injury to children and suggested the implementation of education programs to improve the information (14)(15)(16)(17)(18). Home safety measures implemented by parents have proven effective in preventing childhood injuries (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation